2020
DOI: 10.1371/journal.pntd.0008177
|View full text |Cite
|
Sign up to set email alerts
|

Urticaria and silent parasitism by Ascaridoidea: Component-resolved diagnosis reinforces the significance of this association

Abstract: Urticaria remains a major problem in terms of aetiology, investigation, and management, and although parasitic diseases are considered potential causes, the absence of a consistent link between parasitic infections and skin allergy symptoms leads to the need for a deeper study of parameters that support this association. The objectives of this study were to analyse a possible relationship between parasitism by Ascarididae (Toxocara canis and Anisakis simplex) and the clinical expression of urticaria and to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 64 publications
0
15
0
4
Order By: Relevance
“…A preferential response to some other Anisakis allergens such as Ani s 4 (cystatin), Ani s 5 (SXP/RAL protein), Ani s 11 or Ani s 13 (haemoglobin) 41 43 , can explain that some sera test positive by ImmunoCAP and negative to Trisakis 170. Also, cross-reactions due to Ascaris infections was also reported as a possible cause of detecting sensitization to Anisakis in asymptomatic patients 30 , 44 , 45 , which can be related with IgE responses to pan-allergens as paramyosin (Ani s 2) 31 , 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preferential response to some other Anisakis allergens such as Ani s 4 (cystatin), Ani s 5 (SXP/RAL protein), Ani s 11 or Ani s 13 (haemoglobin) 41 43 , can explain that some sera test positive by ImmunoCAP and negative to Trisakis 170. Also, cross-reactions due to Ascaris infections was also reported as a possible cause of detecting sensitization to Anisakis in asymptomatic patients 30 , 44 , 45 , which can be related with IgE responses to pan-allergens as paramyosin (Ani s 2) 31 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Viñas et al 30 reported that the presence of IgG and IgE antibodies to Ani s 1 and Ani s 3 allergens in serum can aid to differentiate between patients with and without urticaria in regions where Anisakis infections are frequent. Also, cross reactivity between A. simplex allergens and those from house dust mites (HDM) or shellfish among others has been proposed as the origin of positive sIgE to complete A. simplex extract (ImmunoCAP) in asymptomatic population 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study confirmed the immunoreactivity of the heated/autoclaved Anisakis antigens with anti- A. simplex IgG antibodies that were linked to delayed IgG-based allergy. This type of hypersensitivity is associated with chronic urticaria that is a frequent symptom of anisakiasis [ 56 , 57 ]. Detection of IgG antibodies specific to Anisakis is also useful in the serodiagnosis of anisakiasis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A receiver operating characteristic (ROC) curve was constructed to establish the sIgG cut-off value to α-Gal in order to differentiate the patients bitten by ticks who developed AGS from the control groups (atopic subjects and healthy individuals) not bitten by ticks [53].…”
Section: Quantification Of Sige and Sigg Specific Antibodies Against ...mentioning
confidence: 99%